The 2π charged particles analyzer: All‐sky camera concept and development for space missions. Issue 12 (5th December 2016) - Vaisberg, O.; Berthellier, J.‐J.; Moore, T.; Avanov, L.; Leblanc, F.; Leblanc, F.; Moiseev, P.; Moiseenko, D.; Becker, J.; Collier, M.; Laky, G.; Keller, J.; et al.
Abstract: Increasing the temporal resolution and instant coverage of velocity space of space plasma measurements is one of the key issues for experimentalists. Today, the top‐hat plasma analyzer appears to be the favorite solution due to its relative simplicity and the possibility to extend its application by adding a mass‐analysis section and an electrostatic angular scanner. Similarly, great success has been achieved in MMS mission using such multiple top‐hat analyzers to achieve unprecedented temporal resolution. An instantaneous angular coverage of charged particles measurements is an alternative approach to pursuing the goal of high time resolution. This was done with 4‐D Fast Omnidirectional Nonscanning Energy Mass Analyzer and, to a lesser extent, by DYMIO instruments for Mars‐96 and with the Fast Imaging Plasma Spectrometer instrument for MErcury Surface, Space ENvironment, GEochemistry, and Ranging mission. In this paper we describe, along with precursors, a plasma analyzer with a 2 π electrostatic mirror that was developed originally for the Phobos‐Soil mission with a follow‐up in the frame of the BepiColombo mission and is under development for future Russian missions. Different versions of instrument are discussed along with their advantages and drawbacks. Key Points: Instant hemispheric unobscured field of view electrostatic mirror (fish‐eye) is developed The ion energy‐mass analyzers with hemispheric mirror were developed for Phobos‐Soil and BepiColombo missions Advantages and limitations of this element are discusses as well as the perspective of future applications